A Method for Evaluating Dynamical Friction in Linear Ball Bearings - Yusaku Fujii; Koichi Maru; Tao Jin; Preecha P. Yupapin; Somsak Mitatha (My University, 2010)
A method is proposed for evaluating the dynamical friction of linear bearings, whose motion is not perfectly linear due to some play in its internal mechanism. In this method, the moving part of a linear bearing is made to move freely, and the force acting on the moving part is measured as the inertial force given by the product of its mass and the acceleration of its centre of gravity. To evaluate the acceleration of its centre of gravity, the acceleration of two different points on it is measured using a dual-axis optical interferometer.
Keywords: Ball (mathematics); Linear acceleration; Fictitious force; Linear motion; Advanced Measurement and Metrology Techniques